Perancangan Website Sebagai Media Informasi Panti Asuhan Batu Penjuru Kulon Progo - ., Supriyanta; - AMIK BSI Yogyakarta, Eunike Nova Dwi Floren Rindani Nussy (APMMI - Asosiasi Profesi Multimedia Indonesia, 2016)
Abstract - Orphanages Batu Penjuru in Kulon Progo is an institution caring for children who are less able. The existence of orphanages is not widely known because of the lack of information dissemination. The design of this website aims to provide information about Orphanage Batu Penjuru in Kulon Progo. This website is created using Adobe Dreamweaver CS6, PHP and MySQL database by applying the waterfall model. Various data collected, the needs of users and systems in the analysis, then make good software design user interface design and admin, database with ERD, LRS and file specification, and implementation. Website created and then tested using a blackbox testing. Information of the website is expected to be a means to manage data at Orphanage Batu Penjuru in Kulon Progo then served into information to the public.Key Words: Dissemination, Information, OrphanageÂ Abstrak - Panti Asuhan Batu Penjuru di Kulon Progo adalah sebuah lembaga yang merawat anak-anak kurang mampu. Keberadaan panti asuhan tidak banyak diketahui karena kurangnya penyebaran informasi. Desain website ini bertujuan untuk memberikan informasi tentang Panti Asuhan Batu Penjuru di Kulon Progo. Website ini dibuat menggunakan Adobe Dreamweaver CS6, PHP dan database MySQL dengan menerapkan model air terjun. Berbagai data dikumpulkan, kebutuhan pengguna di perhatikan dan sistem di analisis, kemudian membuat software desain antarmuka untuk pengguna dan admin, basis data di rancang dengan ERD dan LRS,Â file spesifikasi dan implementasi. Website yang dibuat kemudian diuji dengan menggunakan pengujian blackbox. Informasi dari website ini diharapkan menjadi media untuk menyampaikan data di Panti Asuhan Batu Penjuru di Kulon Progo kepada masyarakat luas.Kata kunci: Penyebaran, Informasi, Panti Asuhan